Primary solitary cervical amyloidosis: Case report and review of the literature - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2007)
Study Design. A case report and literature review are presented. Objective. To describe and review the clinical presentations, characteristic findings from imaging studies, types, differential diagnosis, prognosis, and treatment of amyloidoma arising within the vertebrae. Summary of Background Data. Amyloidoma can occur in the bone, skin, larynx, lymph nodes, urinary bladder, eye, tongue, and gastrointestinal system. However, amyloidomas affecting the vertebral bones are very rare. To our knowledge, only 3 cases of amyloidoma involving cervical spine have been reported previously. Methods. In this report, we present a case of solitary amyloidosis of the cervical spine. Results. The differential diagnosis of primary solitary spinal amyloidoma includes metastasis, infection, primary bone tumors, plasmocytoma, and Potts abscess. The correct diagnosis can be achieved only after the specific staining of tissue. The prognosis of amyloidosis is related to the specific form of amyloidosis. However, primary solitary amyloidosis has the best prognosis, although a limited number of patients without long-term follow-up studies have been reported. Conclusions. Primary solitary amyloidosis is a rare form of the amyloidosis, which is different from the other forms of amyloidosis because of excellent prognosis with surgical excision. Combined surgical excision and spinal stabilization is the best treatment.
Keywords: amyloidoma; cervical spine; primary solitary amyloidosis; SPINAL-CORD COMPRESSION